Cross-Lagged Associations Between Adolescents’ Depressive Symptoms and Negative Cognitive Style: The Role of Negative Life Events - Kindt, Karlijn C. M. (J Youth Adolesc, 2015)
Previous research has established that cognitive theory-based depression prevention programs aiming change in negative cognitive style in early adolescents do not have strong effects in universal settings. Although theories suggest that a negative cognitive style precedes depressive symptoms, empirical findings are mixed. We hypothesized that negative cognitive style may not predict depressive symptoms in adolescents with normative depressive symptoms. Depressive symptoms, negative cognitive style and dependent negative life events were assessed in young adolescents (N = 1343; mean age = 13.4 years, SD = 0.77; 52.3 % girls) at four time points over an 18-month period. Using a cross-lagged panel design, results revealed that depressive symptoms predicted a negative cognitive style but not vice versa. However, when including dependent negative life events as a variable, depressive symptoms did not prospect a negative cognitive style consistently. When dependent negative life events were used as a time-varying covariate, depressive symptoms and a negative cognitive style were not related. We concluded that negative cognitive style is not predictive of depressive symptoms in a community sample of young adolescents. Moreover, the findings suggest that longitudinal relationships between depressive symptoms and a negative cognitive style are not meaningful when dependent negative life events are not considered.